Pengaruh Kinerja Keuangan dan Risiko Saham terhadap Return Saham - I Putu Edy Arizona; Ni Luh Gde Novitasari; Ni Kadek Dwi Yunita Lestari (Jurnal Inovasi Akuntansi (JIA), 2025)
This study examines the effect of financial performance and stock risk on stock returns in manufacturing companies within the food and beverage subsector listed on the Indonesia Stock Exchange during the 2021–2023 period. The analysis method used is multiple linear regression. This research involves 55 companies as samples, selected using purposive sampling techniques based on specific criteria. The results show that the Current Ratio (CR) does not affect stock returns, while the Debt to Equity Ratio (DER) has a positive effect on stock returns. Return on Assets (ROA) does not affect stock returns. Earnings Per Share (EPS) has a positive effect on stock returns. Beta has a positive effect on stock returns.